Antimicrobial inhibition zone test of purple okra (Abelmoschus esculentus) extract on the growth of gram-negative bacteria - Anggun Wulandari; Dian Kusuma Wardani (Medical Laboratory Analysis and Sciences Journal, 2019)
Okra (Abelmoschus esculentus) contains secondary metabolite compounds that can function as an antibacterial which can inhibit the growth of gram-negative bacteria. This study aims to determine the antimicrobial inhibition zone of purple varieties of okra extract on the growth of gram-negative bacteria (Escherichia coli). This research is an experimental study using a Completely Randomized Design (CRD) with a disk diffusion testing method. The object used was purple okra fruit extract at concentrations of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100% with negative control of DMSO and positive control of chloramphenicol. Inhibition zone diameter measurements are indicated by clear areas, ie areas that are not overgrown with bacteria. The results showed that the most optimum inhibition zone of purple varieties of okra fruit extract was at a concentration of 40%, 50% and 60% with an average value of 6.67 mm.